1966
DOI: 10.1136/jcp.19.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of intestinal absorption of 57Co vitamin B12 by serum counting

Abstract: SYNOPSISThe results of the measurement of vitamin B12 absorption by counting the radioactivity of 5 ml. serum obtained eight to 10 hours after the ingestion of an oral dose of 0 5 ,tg. vitamin B12 labelled with 0-5 ,uc. 57Co are compared with those obtained with the urinary excretion (Schilling) test. Inadequate urine collection and impaired renal function were responsible for low results in the Schilling test in four of the 12 control subjects, and an incomplete urine collection in four patients with pernicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Normalization of absorption was observed in 8 cases of PA when the test was repeated with IF and in remaining 2 patients the values were subnormal but still dis tinctly higher than the original low values. Recent studies of different workers on 57Co-vitamin B12 absorption-plasma level tests gave similar results but with lower plasma radioactivity values and in some cases equivocal results [1,3,6,9,11,13,14], Probably this is due to use of vitamin B12 with lower specific activity and lower dosage (0.5 //c/0.5 ng to 1.0 fic/l.O //g) and differences in methods of calculation of absorbed vitamin B12. This has generally been done per 1000 ml of plasma [1,11,13,14] or expressed as cpm in 4 or 5 ml of plasma [6,9].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Normalization of absorption was observed in 8 cases of PA when the test was repeated with IF and in remaining 2 patients the values were subnormal but still dis tinctly higher than the original low values. Recent studies of different workers on 57Co-vitamin B12 absorption-plasma level tests gave similar results but with lower plasma radioactivity values and in some cases equivocal results [1,3,6,9,11,13,14], Probably this is due to use of vitamin B12 with lower specific activity and lower dosage (0.5 //c/0.5 ng to 1.0 fic/l.O //g) and differences in methods of calculation of absorbed vitamin B12. This has generally been done per 1000 ml of plasma [1,11,13,14] or expressed as cpm in 4 or 5 ml of plasma [6,9].…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies of different workers on 57Co-vitamin B12 absorption-plasma level tests gave similar results but with lower plasma radioactivity values and in some cases equivocal results [1,3,6,9,11,13,14], Probably this is due to use of vitamin B12 with lower specific activity and lower dosage (0.5 //c/0.5 ng to 1.0 fic/l.O //g) and differences in methods of calculation of absorbed vitamin B12. This has generally been done per 1000 ml of plasma [1,11,13,14] or expressed as cpm in 4 or 5 ml of plasma [6,9]. A flushing dose of cold vitamin B12 injection was frequently administered at different time intervals and occasionally carbocal was also given before the test [1,3].…”
Section: Discussionmentioning
confidence: 86%
“…This test is no longer available. Some success has been achieved by monitoring the appearance of Cbl in blood following a dose of 57 CoB 12 (18, 19). However, radioactive Cbl for this use is no longer available.…”
Section: Introductionmentioning
confidence: 99%
“…These results, although disappointing, are not unduly surprising since recent studies have demonstrated the practical advantages of using vi tamin B i2, labelled with 57Co rather than with 38Co [8,10]. This situ ation might well be improved by the use of free 57Co-labelled vitamin B,2 and 58Co-labelled vitamin B^ bound to human gastric juice, (a reversal of the materials used in this study).…”
Section: Jcgmentioning
confidence: 74%
“…It has been shown that there is excellent correlation between 8-hour peak levels of radioactivity in plas ma and 24-hour urinary excretion, in both normal subjects and patients suffering from pernicious anaemia [5,7]. Determination of plasma ra dioactivity has several advantages over measurement of urinary excre tion alone [8,10], A dual isotope ('Dicopac') test for the investigation of suspected vi tamin B12 malabsorption has recently become commercially available. The basis of this test is the simultaneous administration of 2 isotopic forms of radioactive Co-labelled vitamin B12, one of which is free and the other bound to normal human gastric juice.…”
mentioning
confidence: 99%